Relationship between Acoustic Emission and Microcrack Formation in Single Crystals of Hadfield Steel; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Lychagin D. V. Dmitry Vasilievich; Filippov A. V. Andrey Vladimirovich; Moskvichev E. N.; Novitskaia O. S.; Kolubaev E. A. (2018, 2018)
Title screen